Electronic band structure of Bi5O7NO3 and its methyl orange removal mechanism - Abdullah, Eshraq Ahmed (European Journal of Chemistry, 2022)
A detailed study of the electronic band structures and partial density of states of Bi5O7NO3 with different exchange correlation functionals was performed using the generalized gradient approximation. Bi5O7NO3 has two direct energy gap transitions of 2.84 and 3.66 eV at the experimental lattice parameters, revealing a semiconductor characteristic of a crystal. Molecular Mechanics; however, tends to underestimate the band-gap energies with indirect characters. This deviation is due to the slight decrease in the cell edges and the significant increase in the β angle during the optimization process. The mechanism of removal of methyl orange and its derivatives by the Bi5O7NO3 unit cell, which has the same experimental UV-Vis band gap, was later investigated through a DMol3 module. To do that, frontier molecular orbitals, global reactivity parameters, and electrostatic potential surface maps were evaluated. The high values of the electrophilicity indexes hint that the dyes are more reactive and can work as good electrophile species. A molecular packing of dye molecules and the ionic natural of Bi5O7NO3 generate a synergistic effect between π-π stacking, anion-π stacking, cation-π stacking and electrostatic interactions, which are thought to be the driven forces during dye removal.